2016
DOI: 10.1038/srep35054
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Oxytocin Enhances Connectivity in the Neural Circuitry Supporting Social Motivation and Social Perception in Children with Autism

Abstract: Oxytocin (OT) has become a focus in investigations of autism spectrum disorder (ASD). The social deficits that characterize ASD may relate to reduced connectivity between brain sites on the mesolimbic reward pathway (nucleus accumbens; amygdala) that receive OT projections and contribute to social motivation, and cortical sites involved in social perception. Using functional magnetic resonance imaging and a randomized, double blind, placebo-controlled crossover design, we show that OT administration in ASD inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
107
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(114 citation statements)
references
References 79 publications
(109 reference statements)
5
107
1
1
Order By: Relevance
“…In autistic children, a recent study has further shown that intranasal oxytocin acutely strengthens seed-based connectivity from the amygdala and ventral striatum to networks supporting social perception and motivation 9 . There is also evidence that differential expression of OXTR is predicted by early life experiences 135 .…”
Section: Implications For Oxytocin Action and Social Behaviormentioning
confidence: 99%
See 4 more Smart Citations
“…In autistic children, a recent study has further shown that intranasal oxytocin acutely strengthens seed-based connectivity from the amygdala and ventral striatum to networks supporting social perception and motivation 9 . There is also evidence that differential expression of OXTR is predicted by early life experiences 135 .…”
Section: Implications For Oxytocin Action and Social Behaviormentioning
confidence: 99%
“…Importantly, several of these reports suggested a potential therapeutic role for OT administration in cases of trauma 95 , social anxiety 92 , and autism 9,12,94 .…”
Section: Oxytocin and Human Brain Functionmentioning
confidence: 99%
See 3 more Smart Citations